Risk factors of stunting in Indonesian children aged 1 to 60 months - Rizki Aryo Wicaksono; Karina Sugih Arto; Erna Mutiara; Melda Deliana; Munar Lubis; Jose Rizal Latief Batubara (Indonesian Pediatric Society, 2021)
Background The Indonesian province of Aceh has a high prevalence of stunting. Identifying risk factors for stunting may help prevention efforts. The Growth Diagrams of Indonesian Children are a specific tool to diagnose stunting in Indonesian pediatric populations. Objective To determine the risk factors of stunting in children aged 1-60 months using the Growth Diagrams of Indonesian Children. Methods This observational, analytic study with case-control design was conducted in the Lawe Alas District, Southeast Aceh, Indonesia to compare prior risk factors exposure between stunted children (cases) and non-stunted children (controls) from January-April 2018. Subjects were children aged 1-60 months and recruited by consecutive sampling. Results The subjects comprised 97 cases and 97 controls, totaling 194 subjects, internal risk factors of stunting were short birth length (OR 2.87; 95%CI 1.24 to 6.61; P=0.011), inadequate calorie intake (OR 2.37; 95%CI 1.32 to 4.27; P=0.004), non-exclusive breastfeeding (OR 3.64; 95%CI 2.01 to 6.61; P<0.001), chronic diarrhea (OR 6.56; 95%CI 3.33 to 13.01; P<0.001) and upper respiratory tract infections (OR 3.47; 95%CI 1.89 to 6.35; P<0.001). External risk factors of stunting were unimproved sanitation (OR 2.98; 95%CI 1.62 to 5.48; P<0.001), unimproved water sources (OR 2.71; 95%CI 1.50 to 4.88; P=0.001), low family income (OR 2.49; 95%CI 1.38 to 4.49; P=0.002), low paternal educational level (OR 2.98; 95%CI 1.62 to 5.48; P<0.001), low maternal educational level (OR 2.64; 95%CI 1.38 to 5.04; P=0.003), and living in households with >4 family members (OR 1.23; 95%CI 0.69 to 2.17; P=0.469). Regression analysis showed that the dominant risk factor of stunting was chronic diarrhea (OR 5.41; 95%CI 2.20 to 13.29; P<0.001). Conclusion The history of chronic diarrhea and non-exclusive breastfeeding are the main risk factors of childhood stunting.